Effect of Gastro-Hepatic Pack on Biochemical Changes in Type II - Diabetes Mellitus Patients - A Study Protocol for Randomized Controlled Trial - Mani, Mownika; Rathinam, Karthikeyan; Muniyappan, Sathiyanandham; Muthupandi, Pandiaraja; Thirumoorthi, Prabu (Indian Journal of Integrative Medicine, 2025)
Background: Diabetes, particularly Type 2 Diabetes Mellitus (T2DM), is a major global health concern that causes hyperglycaemia due to insulin dysfunction. According to recent studies, the prevalence of diabetes among adults ranges from 7.4% to 10.0%, varying by geography, urban rural settings, and age groups. Gastro hepatic Pack (GH pack) is a naturopathic treatment that involves simultaneously applying cold application on the abdomen and hot application under the lower back wrapped in a woollen cloth. Naturopathic physicians commonly use GH pack intervention to treat patients with liver disorders and diabetes. Hence, we designed this study to investigate the effect of GH pack on biochemical changes in type 2 diabetes mellitus patients. Methods: This study will be performed using a randomised control trial . All eligible subjects will be recruited from International Institute of Yoga and Naturopathy Medical Sciences (IIYNMS), Chengalpattu and randomly assigned (1:1 ratio) to study group or control group using simple random methods with the use of computerised randomisation . The study group (n=40) will undergo GH pack for 20 mins daily,five days a week, for four months. The control group (n=40) will receive yoga and naturopathic interventions in addition to GH pack for every week for 5 days for the course of 4 months. Ethical clearance was obtained from IIYNMS (IECIIYNMS/Approval/004/2023) and registered in the clinical trial registry of India (CTRI/2024/02/063097) Results: The biochemical assessments involved in this study include glycated haemoglobin (HbA1C), liver enzymes such as Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamate Pyruvic Transaminase (SGPT All subjects will undergo baseline and post intervention assessments. Data analysis will be done using appropriate statistical test with R software. The data will be analysed using a paired Student's t test for within group parameters, and an independent t test for between group parameters. In this study, we will use a p (probability) value of 0.05 to determine statistical significance. The mean value of dependent variables will be used to illustrate the outcome in a bar diagram. Conclusion: If the results of this study are significant, GH pack could be used as an adjuvant treatment in the treatment of type 2 diabetes mellitus. The GH pack is a cost effective, simple technique for managing Type II Diabetes mellitus.